Healthcare Information Management Systems Cases, Strategies, and Solutions - Weaver, Charlotte A.; Ball, Marion J.; Kim, George R.; Kiel, Joan M. (Health Informatics, 2016)
This book provides a bold and honest description of the current state of electronic health record (EHR) technologies in acute and primary care settings, and looks at the future through the lens of emerging new technologies, changes in care delivery models and reimbursement policies. This 4th Edition of Healthcare Information Management Systems: Cases, Strategies, and Solutions has been thoroughly updated, as concepts such as Meaningful Use (MU), interoperability, personalized medicine and health IT have had a considerable impact on patient safety and health outcomes. It outlines the issues of EHR adoption under MU and, as anticipated gains in efficiency, quality and costs have not always been seen, it also provides a framework within which solutions to the frustration, dissatisfaction, and growing concerns can be found. Many suggest that a technology sea change is needed with a second generation of EHRs developed on 21st century architectures that more closely match the flexibility and power of mobile and web-based applications available in the general marketplace. Building on the success of its previous three editions, this book will guide healthcare professionals as they confront the technical, organizational, and management issues related to the selection, implementation, and management of healthcare information systems. It will contribute to taking us into a healthcare system that delivers value, is a pleasure to work wit hin, and relieves the taxpayers' burden.